Tropical rehabilitation forest control on water chemistry pattern in Bintulu Sarawak Malaysia - Rosli, Noraini; Gerusu, Geoffery James; Kueh, Roland Jui Heng (Penerbit Universiti Teknologi Malaysia, 2022)
With rapid development in South East Asian countries, there is a risk of serious degradation of stream water quality in areas adjacent to developing city areas, where basic information on toxic heavy metals and acidic compounds (NO3- and SO42-) concentrations and spatiotemporal variation is still unknown in these areas. The concentrations of water quality parameters, major ions, and heavy metals were examined from selected stream in a rehabilitation forest near a developing city having petroleum refinery facility in Bintulu, Sarawak, Malaysia. The concentrations of water quality parameters, major ions, and heavy metals were examined from twelve stream locations in a rehabilitation forest near a developing city with a petroleum refinery facility. Analyses suggested that there is no clear tendency that is detected in heavy metals and basic water properties (EC, DO, BOD, COD, alkalinity and pH) except for turbidity, total suspended solids, and major ion which were high during rainy seasons. Annual means of SO42-, NO3- and NH₄⁺ concentrations were 6.34, 1.05 and 0.24 mg/L. The concentration in K+, Mg2+, Na+ and Ca2+ were 0.61, 1.21, 2.82 and 1.12 mg/L during hot and rainy season. The mean concentration in almost all heavy metals (Mn, Fe, Cu, Zn) were less than 0.01 mg/L. The concentrations of water quality variables in all samples collected across the seasons except for turbidity found within the permissible limit by the WHO and NWQS for Malaysia. Rehabilitation forest might give a positive impact in preserving water quality especially for COD and major ions except SO42-.